Integrated Vision-PLC Control Architecture for High-Performance Delta Robot Sorting in Industrial Automation - Kim-Thanh Vo; Bui-Duc Nghia; Huy-Vu Tran; Thanh-Tuan Huynh; Huy-Bao Nguyen; Phong-Luu Nguyen; Van-Tuan Nguyen; Anh-Quoc Phan; Son-Thanh Phung; Van-Dong-Hai Nguyen; Binh-Hau Nguyen; Van-Hiep Nguyen; Thanh-Binh Nguyen (PT. Teknologi Futuristik Indonesia, 2026)
The rapid development of automation and robotics has increased the demand for high-performance industrial systems, in which Delta robots play a crucial role due to their lightweight structure, high speed, and precise positioning capability. This study aims to design, implement, and evaluate a Delta robot-based product classification system integrating PLC S7-1200 control and Machine vision. The proposed system employs a camera to detect object shape, color, and position on a conveyor, while a PC processes the image data and computes the robot’s inverse kinematics before transmitting control commands to the PLC. A hardware model of the Delta robot was designed and fabricated, and a dual-mode control application was developed to monitor and operate the robot in real time. Experimental results demonstrate that the system achieves stable operation, with a classification speed of up to 20 products per minute and an accuracy of approximately 95.7% for picking and placing tasks. The findings confirm the feasibility and effectiveness of integrating vision-based detection with high-speed parallel robot control for industrial sorting applications. The study also provides a foundation for further optimization in processing speed, mechanical design, and advanced image-processing techniques to enhance system performance in practical manufacturing environments.